GHANAIAN TRADITIONAL WOMEN LEADERS AND SUSTAINABLE DEVELOPMENT: THE CASE OF NADOWLI DISTRICT OF GHANA - Odame, Felicia Safoa (European Scientific Journal, ESJ, 2014)
The unequal power relations between men and women in modern political administration have implications for sustainable development and specifically, under representation of women in traditional institution’s decision making process also has effects on traditional governance. Most traditional authorities in Africa and to be specific are made up of both male and female leaders; however a close examination of the traditional political history of the Dagaabas of Northern Ghana reveals that women traditional leaders have played less significant roles as compared to their counterparts in the south. This is due to some endemic cultural perception of the position of women in public life. Consequently, sensitization and training programmes to empower these women leaders have been made by governments and civil society groups to include them in the governance system and structures of the country. In spite of these efforts the results are low. The extent to which culture plays a role in determining the effects of such efforts is the focus of this paper. It does so by examining the roles, achievements and challenges of contemporary traditional women leaders in Ghana using Nadowli district as a case study. Primary and secondary data were collected and data analysed qualitatively. The women play educational, political and economic roles using the training skills learnt. However, their challenges reflect on their level of achievements which is very low. This demonstrates that cultural belief systems play a role in the impacts of women traditional leaders’ contributions to nation building.